Population census in India: A futuristic perspective - Jain, Seema; Shyam, Madhav (London Routledge, 2025)
The population census serves as the primary data source for demographic analysis, the implementation of social and economic development programmes, administrative activities, and policy decisions, as well as for special surveys and scientific research. This book critically examines key aspects of pre-census activity, including its timing, duration, and method of enumeration. It traces the concepts and definitions adopted by the Census of India since its inception in 1872. The authors explore topics such as census legislation, organisation, administrative structures, training strategies, the instruction manual, and the impact of COVID-19 on the census process.